Odpowiedzi

2010-04-07T14:16:03+02:00
3x+1=16 /-1
3x = 15 /:3
x = 5


2a+4=3a /-3a -4
-a = -4 /*(-1)
a = 4


6b+10=46 /-10
6b = 36 /:6
b = 6


4t+3=6t /-6t -3
-2t = -3 /:(-2)
t = 1 i 1/2


4x+12=3x+21 /-3x -12
x = 9


2y+13=5y+4 /-5y -13
-3y = -9 /:(-3)
y = 3
2010-04-07T14:17:21+02:00
3x+1=16
3x=15 / :3
x=5

2a+4=3a
a=4


6b+10=46
6b=36 / :6
b=6

4t+3=6t
3=2t
t=1.5

2y+13=5y+4
13-4=5y-2y
9=3y /:3
y=3


4x+12=3x+21
x=21-12
x=9

2010-04-07T14:18:46+02:00
3x=16-1 2a-3a=-4 6b=46-10 4t-6t=-3
3x=15/:3 -a=-4/:(-1) 6b=36/:6 -2t=-3/:(-2)
x=5 a=4 b=6 t=1.5

4x-3x=21-12 2y-5y=4-13
x=9 -3y=-9/:(-3)
y=3